Analysis of plastic yield behavior during impact of a rigid sphere on an elastic-perfectly plastic half-space. (1st January 2023) - Yu, Bo; Yin, Xiaochun; Jiang, Liang; Xiao, Xin; Wang, Changliang; Yuan, Hao; Chen, Xiaoao; Xie, Wenhao; Wang, Hui; Ding, Huaiping
Highlights: Numerical analysis of plastic yield behavior in early impact stage based on mesh-refined FE models. Newly observed characteristics of dynamic stress responses in early impact stage. Newly observed evolution modes of initial plastic zone and analysis of plastic yield mechanism. Single-valued dependence of critical impact parameters on normalized impact velocity. Newly proposed velocity criterion for quasi-static impact by considering the limitation of plastic yield. Abstract: This paper investigates the plastic yield behavior during the supersonic, transonic and subsonic stages of impact. The frictionless impacts of a rigid sphere on an elastic-perfectly plastic half-space are simulated by the mesh-refined finite element (FE) models without the assumption of the rigid sphere moving at constant velocity. The dynamical characters of stress field and evolutions of the initial plastic zone are analyzed based on the simulations of a wide range of materials and impact velocities. The plastic yielding is found to occur at all the stages of impact. The present investigation shows that impact-induced waves and fast expansion of contact region have great influence on the high stress regions and the evolution modes of the initial plastic zone. A determination method for the stable yield inception is proposed to avoid the disturbances of the observed local unloading at the beginning of the main plastic zone. The critical parameters at the yield inception are extracted and their dependences upon the normalized impact velocity are analyzed. By considering the limitation of the plastic yield, a new velocity criterion is proposed to solve the critical impact parameters by the quasi-static impact theory. The present investigation shows that the impact with relative high impact velocity makes the plastic yielding shallower and reduces greatly the impact force and dynamic indentation required for yielding. Graphical abstract: Image, graphical abstract